Openness as Organizing Principle: Introduction to the Special Issue. Issue 1 (January 2023) - Splitter, Violetta; Dobusch, Leonhard; von Krogh, Georg; Whittington, Richard; Walgenbach, Peter
'Openness' has become an organizational leitmotif of our time, spreading across a growing set of organizational domains. However, discussions within these specialized domains (e.g. open data, open government or open innovation) treat openness in isolation and specific to the particularities of those domains. The intention of this Special Issue therefore is to foster cross-domain conversations to exchange insights and build cumulative knowledge on openness. To do so, this Introduction to the Special Issue argues that openness should be investigated as a general organizing principle, which we refer to as Open Organizing . Across domains, we define Open Organizing as a dynamic organizing principle along the primary dimension of transparency/opacity and the secondary dimensions of inclusion/exclusion and distributed/concentrated decision rights . As such, Open Organizing raises an overarching problem of design, which results from more specific epistemic, normative and political challenges.